Предмет: Алгебра,
автор: OlgaKarandash
log3(x-6)=log5(x-6)
Как решать
Ответы
Автор ответа:
2
приведём к одному основанию (иначе никак)
log₃(x - 6) = log₃(x -6)/log₃5
log₃(x - 6) - log₃(x -6)/log₃5 = 0 | * log₃5
log₃5*log₃(x - 6) - log₃(x -6) = 0
log₃(x -6)(log₃5 -1) = 0, ⇒ log₃(x - 6) = 0, ⇒x - 6 = 1 ⇒ x = 7
x - 6 > 0, ⇒ x > 6
Ответ:7
log₃(x - 6) = log₃(x -6)/log₃5
log₃(x - 6) - log₃(x -6)/log₃5 = 0 | * log₃5
log₃5*log₃(x - 6) - log₃(x -6) = 0
log₃(x -6)(log₃5 -1) = 0, ⇒ log₃(x - 6) = 0, ⇒x - 6 = 1 ⇒ x = 7
x - 6 > 0, ⇒ x > 6
Ответ:7
Похожие вопросы
Предмет: Биология,
автор: Tsvetochek2202
Предмет: Русский язык,
автор: Pilot228007
Предмет: Английский язык,
автор: 2DKristall
Предмет: Математика,
автор: каktус
Предмет: Обществознание,
автор: оля437